Distortion of auditory space during visually induced self-motion in depth - Teramoto, Wataru; Cui, Zhenglie; Sakamoto, Shuichi; Gyoba, Jiro (Frontiers in Psychology, 2014)
Perception of self-motion is based on the integration of multiple sensory inputs, in particular from the vestibular and visual systems. Our previous study demonstrated that vestibular linear acceleration information distorted auditory space perception [Teramoto et al., 2012, PLoS ONE, 7(6): e39402]. However, it is unclear whether this phenomenon is contingent on vestibular signals or whether it can be caused by inputs from other sensory modalities involved in self-motion perception. Here, we investigated whether visual linear self-motion information can also alter auditory space perception. Large-field visual motion was presented to induce self-motion perception with constant accelerations (Experiment 1) and a constant velocity (Experiment 2) either in a forward or backward direction. During participants’ experience of self-motion, a short noise burst was delivered from one of the loudspeakers aligned parallel to the motion direction along a wall to the left of the listener. Participants indicated from which direction the sound was presented, forward or backward, relative to their coronal (i.e., frontal) plane. Results showed that the sound position aligned with the subjective coronal plane was significantly displaced in the direction of self-motion, especially in the backward self-motion condition as compared with a no motion condition. These results suggest that self-motion information, irrespective of its origin, is crucial for auditory space perception.